PENGARUH LIVE STREAMING TIKTOK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA EL FLOWER STORE BUMI SERPONG DAMAI TANGERANG - Salsabilla, Syifa; Hastono Hastono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of Live streaming and Price on Purchasing Decisions at El Flower Store Bumi Serpong Damai, both partially and simultaneously. The method used is quantitative with 96 respondents as a sample. This study also uses various tests such as validity, reliability, classical assumptions, correlation coefficients, regression, determination, and hypotheses. The results show that Live streaming has a significant effect on purchasing decisions, with a regression equation of Y = 14.818 + 0.648 X1. The t-count value of 9.516> t-table 1.661 and a significance of 0.000 <0.050, so H0 is rejected and H1 is accepted. This means that partially Live streaming has a positive and significant effect. Price also has a significant effect with a regression equation of Y = 9.212 + 1.294 X2. The t-count value of 12.646> t-table 1.661 and a significance of 0.000 <0.050, so H0 is rejected and H2 is accepted. Simultaneously, live streaming and price have a significant effect on purchasing decisions, with the regression equation Y = 2.678 + 0.361 X1 + 0.961 X2. The f-value is 137.343> f-table 3.09 and the significance is 0.000 < 0.050. Therefore, H0 is rejected and H3 is accepted.